Good practices applied to research management at top ranking universities - Marina Tomàs Folch; Trinidad Mentado Labao; Jose María Ruíz Ruíz (Arizona State University, 2015)
This article presents some results of research (EDU2011-26437) into the relationship between various aspects of research universities (management, promotion, visibility, etc.) and research university recognition and international ranking. In relation to this investigation, this article presents several specific good practices of governance and management of common to the highest recognized universities. The five best Spanish universities in international rankings between 2003 and 2013 were evaluated, including interviews with 43 people connected with the general management of research programs and the governing teams comprised of renowned researchers and members of research teams. A qualitative analysis of information through MAXQDA leads to the several conclusions. The best-ranked universities maintained solid practices for sustaining institutional research support and established structures whose purpose is to promote research and scholarship, such as generous funding, networks of transfer, and systematic support for publication, project presentations, and the visibility of successful results.